Design and control of a 3-DOF reaction force compensation mechanism for precision stages - Kim, Hyo Young; Seo, Chang Hoon; Lee, Moon G.; Jo, Jae Hoon; Kim, Tae Gon; Kim, Cheol Ho; Lee, Seok Woo (European Society for Precision Engineering and Nanotechnology, Conference Proceedings - 18th International Conference and Exhibition, EUSPEN 2018, 2018)
Precision stages are widely used in many industrial fields. In recent years, these precision stages are required to have higher speeds, larger sizes, and higher precision for higher productivity and product quality. In particular, these high-performance positioning techniques are classified as one of the most difficult technologies among inspection and production equipment. Vibration control is an important part of high precision positioning technology. Various vibrations disturb the precision system, which can degrade system performance. Therefore, minimizing the vibrations generated by the system helps improve system positioning accuracy. This paper presents a novel active reaction force compensation mechanism for the precision stage. The proposed active reaction force compensation mechanism minimizes vibrations caused by driving linear motors in the precision stage. In this paper, prototype design and experimental results are shown to confirm the possibility. The proposed reaction force compensation mechanism is compact in size, and has the advantage of being able to compensate for reaction force along multiple axes. Because the H-type gantry stage is widely used in the field of ultra-precision positioning systems, the developed mechanism was installed in the H-type gantry stage. The developed mechanism effectively reduces the initial displacement of the system base during acceleration and deceleration.
Keywords: Acceleration and deceleration; Compensation mechanism; High precision positioning; High-speed positioning; Positioning techniques; Precision stage; Ultra precision positioning system; Voice coil motors; High speed positioning; Precision stage; Reaction compensation; Vibration control; Voice coil motor